2007
DOI: 10.1542/peds.2006-1856
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Disease Morbidity Among Young HIV-1–Exposed But Uninfected Infants in Latin American and Caribbean Countries: The National Institute of Child Health and Human Development International Site Development Initiative Perinatal Study

Abstract: Close monitoring of HIV-1-exposed infants, especially those who are anemic at birth or whose mothers have more-advanced HIV-1 disease or who smoked during pregnancy, remains important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
62
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 32 publications
(31 reference statements)
8
62
1
Order By: Relevance
“…Among the neonatal characteristics associated with HIV-1 vertical transmission (Table 2), the present study analysis of the data demonstrates the protective effect of starting AZT prophylaxis immediately after birth, as recommended by the PN-DST/AIDS program in reducing MTCT. Several studies have indicated that even incomplete AZT regimens were effective in protecting newborns from HIV infection (JOÃO et al, 2003;MUSSI-PINHATA et al, 2007). In addition, the association between low birth weight and the HIV transmission observed has also been reported by others, linked mainly to poor nutritional status, anemia or low maternal body mass index.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Among the neonatal characteristics associated with HIV-1 vertical transmission (Table 2), the present study analysis of the data demonstrates the protective effect of starting AZT prophylaxis immediately after birth, as recommended by the PN-DST/AIDS program in reducing MTCT. Several studies have indicated that even incomplete AZT regimens were effective in protecting newborns from HIV infection (JOÃO et al, 2003;MUSSI-PINHATA et al, 2007). In addition, the association between low birth weight and the HIV transmission observed has also been reported by others, linked mainly to poor nutritional status, anemia or low maternal body mass index.…”
Section: Discussionmentioning
confidence: 73%
“…Infectious diseases account for nearly 90% of early childhood deaths in developing countries (MUSSI-PINHATA et al, 2007). In this study, 93% of infants received trimethoprim/sulfamethoxazole in the neonatal period for prophylaxis against Pneumocystis jiroveci pneumonia.…”
Section: Discussionmentioning
confidence: 89%
“…Infants with perinatally transmitted HIV infection are at a high risk of repeated infections, malnutrition and early death. Recent studies have shown that even those infants born to HIV infected mothers (HIV exposed infants) who remain uninfected, have a high morbidity, mortality and prevalence of growth failure [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Programs for vertical transmission prevention of HIV (VTP) have reduced vertical infection to well below 10% (5), therefore nearly 2 million HIV-exposed but uninfected (HEU) infants are born annually. Recent evidence indicates that HEU infants are at a higher risk of infectious morbidity and mortality than their HIV-unexposed, uninfected (HUU) peers (6)(7)(8)(9)(10)(11)(12). The underlying reason(s) for this phenomenon are still unclear but are possibly multifactorial; severity of maternal HIV disease (13), avoidance of breastfeeding (14)(15)(16), and differences in microbial exposures (17) have all been postulated.…”
mentioning
confidence: 99%